1987
DOI: 10.1071/ar9870743
|View full text |Cite
|
Sign up to set email alerts
|

A study of the characteristics of wool follicle and fibre in Merino sheep genetically different in wool production

Abstract: Fourteen Merino ewes from each of two flocks, selectively bred for either high (Fleece Plus) or low (Fleece Minus) clean fleece weight per head, were randomly allotted to two feeding levels (17 v. 34 g kg-1 liveweight) of a good quality diet and offered these levels for 100 days. During the final 42 days, the rate of wool growth and its components were measured in each sheep. The Fleece Plus sheep had a greater density of wool follicles and produced more wool per unit area of skin. The latter trait interacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
4
10
1
Order By: Relevance
“…If the responsiveness of wool growth to nutrition is reduced, not only will total fleece weight be decreased (Williams and Winston 1987;Woolaston 1987), but body growth and composition may also be affected. For example, lines of sheep selected for high or low staple strength were found to differ in the response to nutrition of wool growth rate and skin protein synthesis, and similar differences were also observed in muscle protein synthesis (Adams et al 2000b).…”
Section: Responsiveness To Nutritionmentioning
confidence: 99%
“…If the responsiveness of wool growth to nutrition is reduced, not only will total fleece weight be decreased (Williams and Winston 1987;Woolaston 1987), but body growth and composition may also be affected. For example, lines of sheep selected for high or low staple strength were found to differ in the response to nutrition of wool growth rate and skin protein synthesis, and similar differences were also observed in muscle protein synthesis (Adams et al 2000b).…”
Section: Responsiveness To Nutritionmentioning
confidence: 99%
“…Similarly, certain morphological characteristics of wool follicles, such as depth, curvature and density, are associated with wool production (Nay 1966;Nay and Johnson 1967;Nay and Hayman 1969;Nay 1970;Gonzalez et al 1983), although they are clearly not a direct cause of differences in wool production between sheep. Recent studies indicate that a possible reason sheep differ in wool production under similar environmental conditions may lie in the functioning of the wool follicle (Black 1987;Williams and Winston 1987;Hynd 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a comparison of the parameters affecting individual fibre production, such as the number and size of cells in the germinative region of the bulb, the rate at which these cells divide, the proportion of the bulb cells which enter the fibre and the size and number of the cortical cells, has not been made on two strains of Merinos maintained under similar environmental conditions. In previous wool production studies, differences in wool growth were generated predominantly by nutrition rather than genotype (Schinckel 1962;Short et al 1965;Wilson and Short 1979;Hynd 1989), although Williams and Winston (1987) used sheep from two fleece selection flocks to determine the effects of nutrition, genotype and their interaction on aspects of fibre production. The latter investigation has been extended to studies of two Merino strains differing widely in wool production whilst being maintained under similar environmental and nutritional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bulb size itself is highly correlated with fibre diameter and volume (Rudall 1956;Schinckel 1961;Henderson 1965;Wilson & Short 1979), bulb size in these studies being used to gain indirect assessment of the size of the population of dividing cells. However, Williams & Winston (1987) showed in two Merino lines selected for high and low fleece production that although follicle bulbs had different areas of mitotically active cells, they had the same mean maximum diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these technical limitations, early studies frequently depended on the measurement of a single 1-dimensional parameter (e.g., bulb diameter) which was extrapolated to predict changes in the germinative zone (e.g., Short et al 1965). In some studies this approach has been shown to be flawed (e.g., Williams & Winston 1987); however, no systematic survey has been undertaken of the comparability of the different criteria used to define the boundaries of the germinative region.…”
Section: Introductionmentioning
confidence: 99%